Disturbed genomic imprinting and its relevance for human reproduction: causes and clinical consequences. (18th February 2020) - Elbracht, Miriam; Mackay, Deborah; Begemann, Matthias; Kagan, Karl Oliver; Eggermann, Thomas
Abstract: BACKGROUND: Human reproductive issues affecting fetal and maternal health are caused by numerous exogenous and endogenous factors, of which the latter undoubtedly include genetic changes. Pathogenic variants in either maternal or offspring DNA are associated with effects on the offspring including clinical disorders and nonviable outcomes. Conversely, both fetal and maternal factors can affect maternal health during pregnancy. Recently, it has become evident that mammalian reproduction is influenced by genomic imprinting, an epigenetic phenomenon that regulates the expression of genes according to their parent from whom they are inherited. About 1% of human genes are normally expressed from only the maternally or paternally inherited gene copy. Since numerous imprinted genes are involved in (embryonic) growth and development, disturbance of their balanced expression can adversely affect these processes. OBJECTIVE AND RATIONALE: This review summarises current our understanding of genomic imprinting in relation to human ontogenesis and pregnancy and its relevance for reproductive medicine. SEARCH METHODS: Literature databases (Pubmed, Medline) were thoroughly searched for the role of imprinting in human reproductive failure. In particular, the terms 'multilocus imprinting disturbances, SCMC, NLRP/NALP, imprinting and reproduction' were used in various combinations. OUTCOMES: A range of molecular changes to specific groups of imprinted genes are associated with imprinting disorders, i.e. syndromes with recognisable clinical features including distinctive prenatal features. Whereas the majority of affected individuals exhibit alterations at single imprinted loci, some have multi-locus imprinting disturbances (MLID) with less predictable clinical features. Imprinting disturbances are also seen in some nonviable pregnancy outcomes, such as (recurrent) hydatidiform moles, which can therefore be regarded as a severe form of imprinting disorders. There is growing evidence that MLID can be caused by variants in the maternal genome altering the imprinting status of the oocyte and the embryo, i.e. maternal effect mutations. Pregnancies of women carrying maternal affect mutations can have different courses, ranging from miscarriages to birth of children with clinical features of various imprinting disorders. WIDER IMPLICATIONS: Increasing understanding of imprinting disturbances and their clinical consequences have significant impacts on diagnostics, counselling and management in the context of human reproduction. Defining criteria for identifying pregnancies complicated by imprinting disorders facilitates early diagnosis and personalised management of both the mother and offspring. Identifying the molecular lesions underlying imprinting disturbances (e.g. maternal effect mutations) allows targeted counselling of the family and focused medical care in further pregnancies.